Field Determination of Unsaturated Permeability and Flow Properties through Subgrade Instrumentation - Asif Ahmed; Sahadat Hossain (Geosciences, 2022)
Due to the representation of a particular field condition of soil rather than the real time scenario from laboratory experiments, the selection of unsaturated permeability and flow parameters becomes challenging when conducting numerical modeling. Keeping this in mind, the objective of the study was to determine the permeability in both directions along with the unsaturated flow parameters from field data. Although it is conventional to determine the flow parameters from the curve fitting of laboratory results, a novel approach was carried out during the course of study, wherein field soil water characteristic curves were used to determine the unsaturated flow parameters. Two two-lane roads in Kaufman County and Ellis County, Texas were selected for data acquisition and monitoring in this study. For the investigation of in situ moisture content and matric suction, soil moisture and suction sensors were installed at up to a depth of 4.5 m into the ground, while the precipitation was recorded using rain gauges installed at the sites. Field determination yielded hydraulic conductivity values in the range of 10−4 to 10−5 m/s, representing the rapid flow of water due to desiccation cracks on expansive soil. Field-generated unsaturated flow parameters also indicated variability while constructing the SWCC. Finally, PLAXIS 2D was used for the transient flow analysis. The close agreement of the FE results with the direct field measurements validated the estimated flow parameters. The approach described in the study can be used for determining permeability and unsaturated flow parameter values from field data, which offers a dynamic situation in contrast to the static laboratory condition.